Menguatkan Narasi Kanibalisme (Anthropofagi) dalam Analisis Hyperrealitas Baudrillard pada Cagar Budaya Batu Persidangan di Kecamatan Simanindo - Puspitawati Puspitawati; Dedi Andriansyah; Murni Eva Marlina Rumapea; Erlin Nainggolan; Karina Ita Apulina Br Bangun (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This research was conducted to describe the cannibalism storytelling of the trial stone legend and describe the strategy of the local community in building anthropophagic images of the trial stone legend in Simanindo District. This research was carried out using qualitative research methods with an ethnographic approach. Methods of data collection were carried out through literature studies, observation, and in-depth interviews. There are three narrative versions related to the legend of the trial stones, and the body parts consumed in the rituals carried out at Huta Siallagan. The three narrative versions in question are the community version, the local guide version, and the performance version. Reports related to cannibalism have previously appeared in various historical writings in Sumatra. The story of cannibalism in Huta Siallagan, Simanindo District, is still maintained and is still used as tourism support at this location. The hyperreality of cannibal stories that seem to really happen is strengthened by simulacra patterns (1) narrative through local guides, (2) legend performances trial stone, (3) animism geopark information board, and (4) generalization of the legend of trial stone legend. The stone legend of the trial and the story "Batak people eat people" are not only limited to influencing the economic aspects of society but also have various important values that can be used as a reference by today's society. The values in question are juridical values, political values , and social values.